Frontier Knowledge and Scientific Production: Evidence from the Collapse of International Science* - Iaria, Alessandro; Schwarz, Carlo; Waldinger, Fabian (Quarterly Journal of Economics, 2018)
We show that World War I and the subsequent boycott against Central scientists severely interrupted international scientific cooperation. After 1914, citations to recent research from abroad decreased and paper titles became less similar (evaluated by latent semantic analysis), suggesting a reduction in international knowledge flows. Reduced international scientific cooperation led to a decline in the production of basic science and its application in new technology. Specifically, we compare productivity changes for scientists who relied on frontier research from abroad, to changes for scientists who relied on frontier research from home. After 1914, scientists who relied on frontier research from abroad published fewer papers in top scientific journals, produced less Nobel Prize–nominated research, introduced fewer novel scientific words, and introduced fewer novel words that appeared in the text of subsequent patent grants. The productivity of scientists who relied on top 1% research declined twice as much as the productivity of scientists who relied on top 3% research. Furthermore, highly prolific scientists experienced the starkest absolute productivity declines. This suggests that access to the very best research is key for scientific and technological progress.